The pricing of green bonds : an empirical analysis of spread determinants - Almeida, João Luís de Amorim Ferreira Camelo de (2021)
Green finance is still a very recent topic when we look at the financial and economical scene. This dissertation has as main goal the contribution to the existent theoretical and empirical literature on this topic, more specifically on green bonds. This work intends to perform an analysis of spread determinants of green bonds and compare them to conventional corporate bonds. Thus, we empirically investigate empirically which are the main contractual, macroeconomic, and firms’ accounting and market factors that affect bond spreads. We established a comparison between green bonds and corporate bonds between 2013 and 2020. Our sample includes 14,592 tranches, from which 607 correspond to green bonds and 13,985 to corporate bonds. We conclude that spreads do not differ significantly between green bonds and corporate bonds. Furthermore, we also find that green bonds and conventional corporate bonds are differently influenced by common pricing factors. Finally, we find that less profitable firms and those with lower leverage and higher credit rating choose green bonds over corporate bonds.